TERUMBU KARANG SEBAGAI MOTIF HIAS PADA DESAIN TAS RANSEL - Tri Sari; Sri Marwati (Ornamen, 2022)
Sadranan Beach is one of the beaches in the Special Region of Yogyakarta precisely in Gunung Kidul Regency. Sadranan Beach is famous for its rich coral reefs on its coastline. The beauty of the coral reefs found in Sadranan Beach is not found on other beaches because of the beauty of the coral reefs. However, many fishermen deliberately hunt coral reefs and are used as raw materials for buildings, ornaments, and retrieval of coral animals that use gathul which results in damage to coral reefs. Based on the above events the author is interested in creating a backpack design work with the use of coral reefs as ornamental motifs. The design of the backpack in the Final Task includes four stages of the process of designing and manufacturing a product as well as three stages and six steps of workmanship. The four stages are the feasibility study stage of the design project, the process stage of analysis of aspects of design and design concept, the stage of the process of drafting and making a plan, and the manufacturing process stage. The three stages and six steps of the work, namely the exploration stage, the planning stage and the embodiment stage. The process and results of the design work of this Final Task has three achievements, the first is to be able to design decorative motif designs from coral reefs. The second achievement is being able to design a backpack with ornamental coral reef motifs. The third achievement is to be able to realize the prototype of a backpack with ornamental motifs of coral reefs. The result of this backpack design work is in the form of 4 (four) backpack designs and two (two) prototype backpacks with coral reef decorative motifs. In 4 (four) designs it has the names montipora, acropora, acropoda, and sidesratra.